An Analysis of UAB Meto Interference in English Pronuncation by the X Grade Students at SMA Swasta PGRI - Mansuetus Mola; Rozita Yusniaty Lodo; Yori Imelda Batu (Departement of Mathematics Education, 2023)
This research was conducted to know the pronunciation problems faced by the students, the dominant type of uab meto interference, and the solutions to solve these problems of uab meto interference at SMA Swasta PGRI SoE. The method was used in this study was a qualitative method. The students 20 students from class X were selected as participants in this study. The data obtained written question. Based on the result of the research, the researcher concluded that factors that contribute to uab meto interference in students’ pronunciation among the tenth graders at SMA Swasta PGRI SoE is interlingual factor and the most dominant type of interference. Moreover, the students got some difficulties in pronouncing English and the factors are: they confused with the sound or to pronounce it, uab meto interference their pronunciation.